2014
DOI: 10.28945/1941
|View full text |Cite
|
Sign up to set email alerts
|

Cohort-Based Doctoral Programs: What We Have Learned Over the Last 18 Years

Abstract: This paper assesses student perceptions and includes student reflections pertaining to a cohort model doctoral program in Educational Leadership (EdD) at a Southern university in the United States.Based on the open-ended comments and survey responses from 48 participants who graduated with this degree, the cohort-based doctoral program was found to have met the needs of the students. Conclusions and recommendations are drawn based on extensive literature on cohort based EdD program and findings from this case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 22 publications
(20 reference statements)
0
28
0
Order By: Relevance
“…Their experience concurs with Fenge (2012) and Bista and Cox (2014) that 'cohortness' is key to a successful professional doctorate journey. We suggest that the support offered among the doctoral colleagues in this Facebook group has enhanced the cohort identity (Fenge, 2012): each knows what is happening in others' lives external to the doctoral process, and such knowledge allows the group to be caring on both an academic and a personal level.…”
Section: Reflection 1: Bonding Of the Group -The Value Of 'Cohortness'mentioning
confidence: 59%
See 1 more Smart Citation
“…Their experience concurs with Fenge (2012) and Bista and Cox (2014) that 'cohortness' is key to a successful professional doctorate journey. We suggest that the support offered among the doctoral colleagues in this Facebook group has enhanced the cohort identity (Fenge, 2012): each knows what is happening in others' lives external to the doctoral process, and such knowledge allows the group to be caring on both an academic and a personal level.…”
Section: Reflection 1: Bonding Of the Group -The Value Of 'Cohortness'mentioning
confidence: 59%
“…The Doctorate in Education (EdD) at this university is a taught programme, using a closed-cohort model (Bista & Cox, 2014). There are currently around 40 students enrolled on the programme, with an intake of approximately eight students per year.…”
Section: Introduction and Review Of The Literaturementioning
confidence: 99%
“…Participants reportedly obtained previously unobtainable forms of capital -cultural, social, and symbolic. Although the Forum does not accord with the conventional 'cohort-based model' (Bista & Cox, 2014;Lei, Gorelick, Short, Smallwood, & Wright-Porter, 2011) in definition, benefits emerging from the Forum strongly align with those produced through the cohort-based model. For example, learning within a cohort nurtures interpersonal development and personal attributes, fosters management and communication skills (S. Freeman & Kochan, 2012), offers an integral part of personal and professional support for academic interactions (Nimer, 2009), and develops a shared learning community through a strong social and professional network (Hyatt & Williams, 2011;Williams, Simpson, & Cunningham, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…Among the positive consequences students experience are being able to share experiences with their fellow cohort members (Lei, Gorelick, Short, Smallwood, & WrightPorter, 2011) and having a supportive and shared environment in which to pursue their degree (Bista & Cox, 2014;Sax, 2008;Tokuno, 2008). In contrast, dominant and potentially negatively personalities may arise in the classroom as the same students, being in the cohort together, see one another in every class (McPhail, Robinson, & Scott, 2008), and while these students always see one another in class, limited additional time for collaborative research outside of the classroom exists given the nature of these students as professionals, family members, and working adults (Bernauer et al, 2013).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Studies have indicated that the support that cohort members received from their classmates have been beneficial for older, part-time students, married students, and students who are parents with home and childcare responsibilities (Sax, 2008;Tokuno, 2008). A study conducted by Bista and Cox (2014) cited the friendships and family-like atmosphere developed in one cohort model as assets to the approach. These social factors play an important role in student success as well as the overall success of cohort models.…”
Section: Doctoral Cohort Modelmentioning
confidence: 99%